Neonatal septicemia: bacteriological profile in a tertiary level hospital in South India - Vijayan, Soja; Narayanan, Deepa S.; Velayudhan Nair, Gopalan A. (International Journal of Research in Medical Sciences, 2019)
Background: Early onset bacterial sepsis remains a major cause of neonatal morbidity and death. The choice of antibiotic for an infant with sepsis depends on the predominant bacterial pathogens and the antibiotic susceptibility profiles for the microorganisms causing disease in a particular geographic region. The purpose of this study was to analyze the bacteriological profile and antibiotic sensitivity pattern of neonatal septicemia in our neonatal unit. Methods: A descriptive cross sectional study carried was out at the NICU of a tertiary level hospital in South India for a period of one year. Results: Clinically suspected septicemia comprised 18.14% of total NICU admissions. Organism was isolated by blood culture in 14.9% of cases. The most common organisms causing septicemia were Coagulase negative Staphylococci, Klebsiella and Staphylococcus aureus. Gram positive isolates were most sensitive to Vancomycin (100%) while the gram negative isolates were most sensitive to Amikacin. Resistance to Crystalline Penicillin, Ampicillin and 3rd generation cephalosporins was high. Conclusions: The most common organism isolated in septicemia was Coagulase negative staphylococcus in our NICU. Gram positive isolates were most sensitive to Vancomycin (100%) while the gram negative isolates were most sensitive to Amikacin. High resistance to commonly used antibiotics is worrisome. There should be a constant surveillance of the common microbes and their sensitivity pattern in each NICU and the antibiotic protocols should be periodically reviewed. Rational use of antibiotics and preventive measures like hand washing is the need of the hour.